Collective Social Entrepreneurship: Collaboratively Shaping Social Good - Montgomery, A. Wren; Dacin, Peter A.; Dacin, M. Tina (2012)
In this paper, we move beyond the typical focus on the role of individuals in leading social change to examine “collective social entrepreneurship”, the role multiple actors collaboratively play to address social problems, create new institutions, and dismantle outdated institutional arrangements. Specifically, we examine collective social entrepreneurship across a diverse range of collaborative activities including movements, alliances and markets for social good. We identify resource utilization approaches and three associated sets of activities that illustrate the work of collective social entrepreneurs—framing, convening, and multivocality. Using illustrative case studies to examine the phenomenon, we highlight the capacity of collective action across sectors to create markets, institutions and organizations and, to derive success by resonating through embeddedness in broader social movements.
Keywords: Cross-sectoral collaboration; Collective Action; Collective social entrepreneurship